Polyaluminum chloride composite flocculant for phosphorus-containing wastewater treatment and preparation method thereof

By preparing a composite flocculant of modified chitosan and polyaluminum chloride, and combining ethylenediamine branching and magnetic core-shell adsorption, the problems of small floc size and high heavy metal ion content were solved, achieving efficient phosphorus removal and low metal ion content flocculation effect.

CN121044692APending Publication Date: 2025-12-02SHANDONG CHUANGXING WATER TREATMENT EQUIPMENT CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202511172636.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing aluminum-based flocculants produce small flocs with small surface areas during phosphorus removal, and the flocculated water has a high content of metal ions, making it difficult to effectively reduce the heavy metal content of sludge.

Method used

By combining modified chitosan with polyaluminum chloride and grafting ethylenediamine to form a branched polymer, the amino and hydroxyl groups of the modified chitosan are used to improve the flocculation and sedimentation effect, and the magnetic core and shell adsorb heavy metal ions to reduce the metal ion content in the water.

Benefits of technology

It achieves highly efficient phosphorus removal (removal rate ≥99.2%), while significantly reducing the content of heavy metal ions in the flocculated water, meeting environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a polyaluminum chloride composite flocculant for phosphorus-containing wastewater treatment and a preparation method thereof, and belongs to the technical field of wastewater treatment.The preparation method of the composite flocculant comprises the following steps that modified chitosan is added into a polyaluminum chloride solution, after heating and stirring reaction, ethidene diamine is dropwise added into the solution, stirring reaction continues for 6 h, a product is precipitated with ethyl alcohol, and the polyaluminum chloride composite flocculant is obtained. And washing with acetone, and drying at 50 DEG C until the weight is constant to obtain the polyaluminum chloride composite flocculant. According to the polyaluminum chloride composite flocculant prepared by the preparation method disclosed by the invention, the modified chitosan is compounded with polyaluminum chloride, and then the compound flocculant is obtained by branching with ethidene diamine, and the compound flocculant has an excellent effect in the aspect of phosphorus-containing wastewater treatment. The magnetic core shell is connected to the surface of chitosan of a three-dimensional network structure, the magnetic core shell is prepared by coating nano Fe3O4 with tetraethyl silicate, and the magnetic core shell is beneficial to reducing the content of metal ions in flocculated clear water in the water treatment process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology, specifically relating to a polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater and its preparation method. Background Technology

[0002] The discharge of phosphorus-containing industrial wastewater and domestic sewage, among other human activities, severely interferes with and affects the natural phosphorus cycle, causing excessive phosphorus levels in water bodies and posing potential harm to the environment, flora and fauna, and human health. Among current phosphorus removal methods, chemical flocculation and sedimentation is a relatively mature approach. Its basic principle is to add chemical agents to react with PO4 in the water. 3- -P reacts to form insoluble phosphate precipitates, which in turn react with PO4. 3- -P separation and removal has advantages such as simple operation, good phosphorus removal effect, and controllable cost. Among them, common chemical flocculants include calcium salt flocculants, aluminum flocculants, iron flocculants, and organic polymer flocculants.

[0003] Polyaluminum chloride (PAC) is currently the most mature, widely used, and best-selling chemical flocculant on the market, offering advantages such as low dosage, high turbidity removal, and less sludge. While PAC has strong electrical neutrality, the resulting flocs are relatively small, resulting in a smaller surface area for further flocculation. Furthermore, the flocculated water contains a relatively high concentration of metal ions, such as aluminum ions, some of which originate from PAC itself. Existing technologies have addressed these two issues extensively. Among these, combining chitosan (CTS) with PAC, utilizing chitosan's adsorption capacity to improve the flocculation and sedimentation effect of the composite flocculant, shows broad research potential. A search reveals the following research achievements regarding the CTS-PAC composite: Chinese patent CN104229961B discloses an environmentally friendly composite flocculant for tap water consisting of chitosan quaternary ammonium salt and polyaluminum chloride. This invention produces a complementary and synergistic effect through the combination of chitosan quaternary ammonium salt solution and polyaluminum chloride solution. The chitosan quaternary ammonium salt is positively charged after dissolution, which can promote the destabilization and sedimentation of colloids. The free amino groups in the chitosan quaternary ammonium salt can reduce the aluminum ion content in the water through chelation.

[0004] Chinese patent CN107500393B discloses a polyaluminum chloride-chitosan composite flocculant, its preparation method, and its application. This invention first crosslinks chitosan with sodium polyphosphate, then copolymerizes the phosphate groups in sodium polyphosphate with polyaluminum chloride to form a chitosan-polyphosphate-polyaluminum chloride composite flocculant. This enhances the binding and bridging effect, strong charge neutralization effect, and significant selective flocculant effect. Similar to Chinese patent CN104229961B, it utilizes -N... 3+ This enhances the effect of forming stable complexes with metal ions and causing them to settle.

[0005] Chinese patent CN109319895B discloses a nano-chitosan-modified polyaluminum chloride and its preparation method. This invention utilizes nano-chitosan particles to modify polyaluminum chloride, retaining the charge neutralization effect of aluminum chloride, enhancing its electrostatic cluster effect, and introducing the flocculation effect of chitosan.

[0006] Chinese patent CN115991529B discloses a production process for polyaluminum chloride-based flocculants. This invention patent uses modified chitosan and polyaluminum chloride to prepare flocculants, similar to Chinese patent CN107500393B. It uses sodium polyphosphate to modify chitosan, and then uses phosphate ions in the sodium polyphosphate solution to copolymerize polyaluminum chloride to improve the flocculation and sedimentation effect.

[0007] Most of the aforementioned research and development achievements utilize the advantages of chitosan as a cationic flocculant to improve the flocculation and sedimentation effect of composite flocculants. At the same time, the amino groups in chitosan are used to reduce the residual aluminum ion content. There is still room for improvement in reducing the heavy metal content of flocculated sludge. Summary of the Invention

[0008] The present invention aims to improve the phosphorus removal and sedimentation effect of composite flocculants in wastewater, while reducing the heavy metal content of flocculated sludge. Therefore, one objective of the present invention is to provide a polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater, and another objective of the present invention is to provide a method for preparing the above-mentioned composite flocculant.

[0009] The objective of this invention can be achieved through the following technical solutions: A method for preparing a polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater includes the following steps: Modified chitosan was added to a 30% polyaluminum chloride solution, the temperature was raised to 55-60℃, and the mixture was stirred for 4 hours. Ethylenediamine was then added dropwise, and the mixture was stirred for another 6 hours. After the reaction was completed, the product was precipitated with ethanol, washed with acetone, and then dried at 50℃ to constant weight to obtain the polyaluminum chloride composite flocculant.

[0010] Furthermore, the ratio of the polyaluminum chloride solution, modified chitosan, and ethylenediamine is 200mL: 15-18g: 3-4mL.

[0011] Furthermore, the modified chitosan is prepared by the following steps: Anhydrous ethanol was added to the pretreated magnetic core shell, and the mixture was ultrasonically dispersed for 30 min. The temperature was raised to 76-80℃, and 25% ammonia was added while stirring at a constant temperature. Chitosan was added within 5 min, and the reaction was carried out for 2 h. After the reaction was completed, the mixture was washed with anhydrous ethanol and dried to obtain modified chitosan.

[0012] Furthermore, the pretreatment process of the magnetic core shell: The magnetic core shell was vacuum dried at 200℃ for 30 min and then cooled to obtain the pretreated magnetic core shell.

[0013] Furthermore, the ratio of the pretreated magnetic core shell, anhydrous ethanol, 25% ammonia, and chitosan is 8-10g:400mL:100mL:50g.

[0014] In the preparation process of the modified chitosan described above, the magnetic core shell is first pretreated. The surface of the magnetic core shell contains a large number of silanol groups, which are combined with water molecules by hydrogen bonds to form multilayer bound water. In this invention, the magnetic core shell is vacuum dried at 200°C, which helps to remove the outer layer bound water. The principle is as follows: by removing the outer layer bound water, the distribution width of the outer layer silanol groups of the magnetic core shell is reduced, thereby improving the tightness of the binding between the magnetic core shell and chitosan.

[0015] .

[0016] Furthermore, the magnetic core shell is prepared by the following steps: Anhydrous ethanol was added to nano-Fe3O4, and the mixture was ultrasonically dispersed. Then, 25% ammonia water was added, followed by the addition of tetraethyl silicate. The mixture was stirred for 8-10 hours to obtain a coating. After washing, drying, and pulverizing, the coating was used to obtain a magnetic core-shell.

[0017] Furthermore, the ratio of nano-ferric oxide, anhydrous ethanol, 25% ammonia water and tetraethyl silicate is 20g:500mL:50mL:48-50mL.

[0018] In the preparation process of the above-mentioned magnetic core shell, the present invention utilizes ammonia water to catalyze the hydrolysis of tetraethyl silicate (TEOS) in a mixed solution of ethanol and water. The generated SiO2 is deposited on the surface of magnetic nano Fe3O4 particles to form a spherical SiO2 coating layer. After cleaning and drying, the magnetic core shell is obtained. The -Si-O-Si- structure on the surface of the magnetic core shell has a large number of silanol groups, which provide reaction sites for subsequent synthesis.

[0019] A polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater is prepared by the above method.

[0020] The beneficial effects of this invention are: This invention prepares a polyaluminum chloride composite flocculant by using modified chitosan to composite polyaluminum chloride, and then branching it with ethylenediamine to obtain the composite flocculant. The composite flocculant has excellent effect in the treatment of phosphorus-containing wastewater (removal rate ≥99.2%).

[0021] First, polyaluminum chloride (PAC) possesses strong bridging and adsorption properties. During hydrolysis, it undergoes physicochemical processes such as coagulation, adsorption, and precipitation, exhibiting high charge neutralization and bridging effects on colloids and particulate matter in water. Its phosphorus removal process involves two main reaction processes: first, Al… 3+ With PO4 3- -P reaction produces AlPO4 precipitate; followed by Al 3+ A hydrolysis reaction occurs, during which positively charged, mononuclear hydroxyl complexes (Al(OH)) are formed. 2+ Al(OH)2 + AlO2 - (etc.) and polynuclear hydroxyl complexes (Al n (OH) m (3n-m)+ (where n>1, m≤3n) exists, and after a series of actions such as van der Waals forces and net trapping, the phosphorus removal effect is significant.

[0022] Then, the abundant amino and hydroxyl groups in the chitosan molecules of the modified chitosan improve the flocculation and sedimentation effect of the composite flocculant through adsorption and coordination. At the same time, through the coordination between active amino groups and aluminum ions, aluminum ions released by polyaluminum chloride are adsorbed, reducing the content of residual metal ions in the clear water after flocculation treatment of phosphorus-containing wastewater. In this invention, a magnetic core shell is attached to the surface of the three-dimensional network structure of chitosan. The magnetic core shell is prepared by coating nano-Fe3O4 with tetraethyl orthosilicate. During water treatment, the magnetic core shell can selectively adsorb aluminum ions and other heavy metal ions in the water, which helps to reduce the content of metal ions in the clear water after flocculation.

[0023] Finally, this invention utilizes an amidation reaction to graft ethylenediamine onto the surface of modified chitosan, ultimately preparing a branched polymer composite flocculant, which helps improve the flocculation and sedimentation effect of the composite flocculant. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1: Preparation of modified chitosan: S1. Add 20g of nano-Fe3O4 (50nm) to reactor A, then add 500mL of anhydrous ethanol, and ultrasonically disperse for 30min. Then add 50mL of commercially available 25% ammonia water (mass fraction) as a catalyst, and then add 48mL of tetraethyl orthosilicate (TEOS) dropwise. Stir the reaction for 8h to obtain the coating. The coating is washed with anhydrous ethanol and ammonia water, and then dried and pulverized to obtain a magnetic core and shell. S2. The magnetic core shell was vacuum dried at 200℃ for 30 min. After cooling, the pretreated magnetic core shell was obtained. 8 g of the pretreated magnetic core shell was placed in a reactor. 400 mL of anhydrous ethanol was added to the reactor and ultrasonically dispersed for 30 min. Then the reactor was heated to 76℃ and 100 mL of commercially available 25% ammonia water (mass fraction) was added while stirring at a constant temperature. 50 g of chitosan (purchased from Tianjin Bodi Chemical Co., Ltd.) was added within 5 min. The reaction was carried out for 2 h. After the reaction was completed, the mixture was washed with anhydrous ethanol and dried to obtain modified chitosan.

[0026] Example 2: Preparation of modified chitosan: S1. Add 20g of nano-Fe3O4 (50nm) to reactor A, then add 500mL of anhydrous ethanol, and ultrasonically disperse for 30min. Then add 50mL of commercially available 25% ammonia water (mass fraction) as a catalyst, and then add 49mL of tetraethyl orthosilicate (TEOS) dropwise. Stir the reaction for 9h to obtain the coating. The coating is washed with anhydrous ethanol and ammonia water, and then dried and pulverized to obtain a magnetic core and shell. S2. The magnetic core shell was vacuum dried at 200℃ for 30 min. After cooling, the pretreated magnetic core shell was obtained. 9 g of the pretreated magnetic core shell was placed in a reactor. 400 mL of anhydrous ethanol was added to the reactor and ultrasonically dispersed for 30 min. Then the reactor was heated to 78℃ and 100 mL of commercially available 25% ammonia water (mass fraction) was added while stirring at a constant temperature. 50 g of chitosan (purchased from Tianjin Bodi Chemical Co., Ltd.) was added within 5 min. The reaction was carried out for 2 h. After the reaction was completed, the mixture was washed with anhydrous ethanol and dried to obtain modified chitosan.

[0027] Example 3: Preparation of modified chitosan: S1. Add 20g of nano-Fe3O4 (50nm) to reactor A, then add 500mL of anhydrous ethanol, and ultrasonically disperse for 30min. Then add 50mL of commercially available 25% ammonia water (mass fraction) as a catalyst, and then add 50mL of tetraethyl silicate (TEOS) dropwise. Stir and react for 10h to obtain the coating. The coating is washed with anhydrous ethanol and ammonia water, and then dried and pulverized to obtain a magnetic core and shell. S2. The magnetic core shell was vacuum dried at 200℃ for 30 min. After cooling, the pretreated magnetic core shell was obtained. 10 g of the pretreated magnetic core shell was placed in a reactor. 400 mL of anhydrous ethanol was added to the reactor and ultrasonically dispersed for 30 min. Then the reactor was heated to 80℃ and 100 mL of commercially available 25% ammonia water (mass fraction) was added while stirring at a constant temperature. 50 g of chitosan (purchased from Tianjin Bodi Chemical Co., Ltd.) was added within 5 min. The reaction was carried out for 2 h. After the reaction was completed, the mixture was washed with anhydrous ethanol and dried to obtain modified chitosan.

[0028] Example 4: Preparation of polyaluminum chloride composite flocculant: 200 mL of polyaluminum chloride solution (basicity 85.2%, purchased from Gongyi Baolai Water Treatment Materials Factory, Zhengzhou City, Henan Province, alumina mass fraction 30.0%) was added to the reactor, followed by 15 g of the modified chitosan prepared in Example 1. The reactor was heated to 55 °C and stirred for 4 h. Then, 3 mL of ethylenediamine was added dropwise, and the reaction was continued for 6 h. After the reaction was completed, the product was precipitated with ethanol, washed with acetone, and dried at 50 °C to constant weight to obtain polyaluminum chloride composite flocculant.

[0029] Example 5: Preparation of polyaluminum chloride composite flocculant: 200 mL of polyaluminum chloride solution (basicity 85.2%, purchased from Gongyi Baolai Water Treatment Materials Factory, Zhengzhou City, Henan Province, alumina mass fraction 30.0%) was added to the reactor, followed by 17 g of the modified chitosan prepared in Example 2. The reactor was heated to 58 °C and stirred for 4 h. Then, 4 mL of ethylenediamine was added dropwise, and the reaction was continued for 6 h. After the reaction was completed, the product was precipitated with ethanol, washed with acetone, and dried at 50 °C to constant weight to obtain polyaluminum chloride composite flocculant.

[0030] Example 6: Preparation of polyaluminum chloride composite flocculant: 200 mL of polyaluminum chloride solution (basicity 85.2%, purchased from Gongyi Baolai Water Treatment Materials Factory, Zhengzhou City, Henan Province, alumina mass fraction 30.0%) was added to the reactor, followed by 18 g of the modified chitosan prepared in Example 3. The reactor was heated to 60 °C and stirred for 4 h. Then, 4 mL of ethylenediamine was added dropwise, and the reaction was continued for 6 h. After the reaction was completed, the product was precipitated with ethanol, washed with acetone, and dried at 50 °C to constant weight to obtain polyaluminum chloride composite flocculant.

[0031] Comparative Example 1 The difference between Comparative Example 1 and Example 4 is that ethylenediamine is removed, while the rest of the preparation process remains the same.

[0032] Comparative Example 2 The difference between Comparative Example 2 and Example 5 is that the modified chitosan was replaced with chitosan (purchased from Tianjin Bodi Chemical Co., Ltd.), while the rest of the preparation process remained the same.

[0033] The polyaluminum chloride composite flocculants prepared in Examples 4-6 and Comparative Examples 1-2 were used to treat phosphorus-containing wastewater. The treatment process is as follows: The phosphorus-containing wastewater studied in this invention originated from the processing workshop and domestic sewage of a seafood processing plant in China. To ensure the freshness of the fish products, the processing workshop artificially added a water-retaining agent. The presence of this agent resulted in a high concentration of phosphorus in the wastewater, with total phosphorus (TP) reaching 1000 mg / L. The main component of the water-retaining agent was tripolyphosphate. After anaerobic microbial treatment, the polymeric phosphate was converted into orthophosphate (PO4). 3- -P), the phosphorus in the wastewater discharged from this processing workshop currently exists mainly in the form of orthophosphate. The main characteristics of the wastewater are high concentrations of orthophosphate and excessive levels of heavy metals, making it particularly difficult to treat as chemical wastewater. Specifically, the water quality analysis of the phosphorus-containing wastewater sampled in this invention is shown in Table 1 below: Table 1. Water quality analysis of phosphorus-containing wastewater (unit: mg / L (except pH))

[0034] The phosphorus removal effect of the five groups of polyaluminum chloride composite flocculants was tested. The experimental procedure for each group of polyaluminum chloride composite flocculants was as follows: 500 mL of wastewater was added to three 1000 mL beakers, and 12.5 g, 15 g, and 17.5 g of polyaluminum chloride composite flocculant were added, i.e., three concentration gradients were set, namely 25, 30, and 35 g / L. The mixture was stirred rapidly (180 r / min) for 24 h and then slowly stirred (80 r / min) for 30 min, followed by standing for 12 h. Various indicators of the upper wastewater were measured. The results showed that the heavy metal content in the upper wastewater of the nine groups after phosphorus removal in Examples 4-6 all met the national standard GB5749-85. The phosphorus removal results are shown in Table 2 below. Table 2

[0035] As shown in Table 2, the polyaluminum chloride composite flocculants prepared in Examples 4-6 of this invention all exhibit excellent dephosphorization effects (removal rate ≥99.2%). Comparing the water quality analysis results of Example 4 and Comparative Example 1, it can be seen that grafting ethylenediamine helps to improve the dephosphorization flocculation effect of the aluminum chloride composite flocculant, possibly because it increases the surface area of ​​the flocs. Comparing the water quality analysis results of Example 5 and Comparative Example 2, it can be seen that the improved treatment of chitosan in this invention helps to improve the dephosphorization flocculation effect of the aluminum chloride composite flocculant, possibly because it increases the active groups on the surface of the polyaluminum chloride composite flocculant, thereby improving the dephosphorization flocculation effect.

[0036] It should be noted that, in this document, terms such as “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0037] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater, characterized in that, Includes the following steps: Modified chitosan was added to a 30% polyaluminum chloride solution, the temperature was raised to 55-60℃, and the mixture was stirred for 4 hours. Ethylenediamine was then added dropwise, and the mixture was stirred for another 6 hours. After the reaction was completed, the product was precipitated with ethanol, washed with acetone, and then dried at 50℃ to constant weight to obtain the polyaluminum chloride composite flocculant.

2. The preparation method of the polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater according to claim 1, characterized in that, The ratio of the polyaluminum chloride solution, modified chitosan, and ethylenediamine used is 200mL: 15-18g: 3-4mL.

3. The preparation method of the polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater according to claim 1, characterized in that, The modified chitosan is prepared by the following steps: Anhydrous ethanol was added to the pretreated magnetic core shell, and the mixture was ultrasonically dispersed for 30 min. The temperature was raised to 76-80℃, and 25% ammonia was added while stirring at a constant temperature. Chitosan was added within 5 min, and the reaction was carried out for 2 h. After the reaction was completed, the mixture was washed with anhydrous ethanol and dried to obtain modified chitosan.

4. The preparation method of the polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater according to claim 3, characterized in that, The pretreatment process of the magnetic core shell: The magnetic core shell was vacuum dried at 200℃ for 30 min and then cooled to obtain the pretreated magnetic core shell.

5. The preparation method of the polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater according to claim 3, characterized in that, The ratio of the pretreated magnetic core shell, anhydrous ethanol, 25% ammonia, and chitosan is 8-10g:400mL:100mL:50g.

6. The preparation method of the polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater according to claim 3, characterized in that, The magnetic core shell is prepared by the following steps: Anhydrous ethanol was added to nano-Fe3O4, and the mixture was ultrasonically dispersed. Then, 25% ammonia water was added, followed by the addition of tetraethyl silicate. The mixture was stirred for 8-10 hours to obtain a coating. After washing, drying, and pulverizing, the coating was used to obtain a magnetic core-shell.

7. The preparation method of the polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater according to claim 6, characterized in that, The ratio of nano-ferric oxide, anhydrous ethanol, 25% ammonia, and tetraethyl silicate is 20g:500mL:50mL:48-50mL.

8. A polyaluminum chloride composite flocculant for treating phosphorus-containing wastewater, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.

Citation Information

Patent Citations

  • Environmentally friendly composite flocculant of chitosan quaternary ammonium salt and polyaluminum chloride for tap water

    CN104229961B

  • A polyaluminum chloride-chitosan composite flocculant, its preparation method and application

    CN107500393B

  • A nano-chitosan-modified polyaluminum chloride and its preparation method

    CN109319895B

  • A production process for a polyaluminum chloride-based flocculant

    CN115991529B

  • Preparation of magnetic chitosan composite adsorption material and application in dye wastewater treatment

    CN106582560A